Combatting the opioid epidemic: Baltimore's experience and lessons learned. (19th July 2017) - Wen, Leana S; Warren, Katherine E
Abstract: In the midst of a national opioid crisis, Baltimore City witnessed 393 deaths from drug and alcohol overdose in 2015. With an estimated 25 000 residents who are addicted to heroin or other opioids, Baltimore has been profoundly affected by the opioid epidemic. Other resources have commented on federal, state-based, and provider responses to the opioid crisis. This article examines what may be done at the city level based on the experiences of the Baltimore City Health Department. Local jurisdictions must play a critical role in addressing the U.S. opioid crisis through public health coalitions, overdose prevention, treatment expansion, and anti-stigma education.